Prospective study of primary cesarean section in multigravida - S Momon Singh; Tina Singh; Vaidehi Thakur (New Indian Journal of OBGYN, 2023)
Background: Progress in obstetrics has been associated with an increased incidence of cesarean section (CS). Primary CS in a multipara means the first CS performed in woman who has delivered vaginally at least once previously and it is associated with a number of maternal and foetal indications. Objectives: The present research was undertaken to study the incidence and indications of primary CS in multigravida. Method: This prospective observational study was conducted in total 510 booked cases of multigravida reported to antenatal OPD with gestational age >28 weeks and previous vaginal deliveries and no cesarean delivery or any other scar on uterus. Results: Primary CS was performed in 75(14.7%) multigravida women. Majority of cases (48%) with primary CS belonged to 26-30 years age group. The incidence of primary CS in emergency and elective cases was 74.7% and 25.3% respectively. Maternal and fetal indications contributed 44% and 56% of the total cases respectively. Fetal distress (26.7%), malpresentation (18.7%) and failed induction (14.7%) for various co-morbidities were the commonest indications of primary CS. Conclusion: Fetal distress is a major contributor to primary CS in multigravida. Proper antenatal evaluation with early detection and management of high risk cases can reduce the likelyhood of intrapartum fetal distress.